Properties and prototype applications of polyester composites reinforced with woven fabric of Agave vera-cruz fiber - Ayyallu Neelaram Balaji; Mariappan Kanaga Vijaya Karthikeyan; Venkataraman Vignesh; Ayyallu Balaji Madhavan; Nadir Ayrilmis; Kwang-Hyun Ryu; Hyun-Joong Kim (Journal of Wood Science)
Abstract This study focused on the mechanical and thermal properties of polyester composites reinforced with woven fabric of Agave vera-cruz fibers. The woven fabrics were fabricated in various forms of randomly oriented Agave vera-cruz fiber, intentionally twisted Agave vera-cruz fiber rope, and Agave vera-cruz fiber rope. Polyester composites reinforced with woven fabrics were prepared by hand lay-up and and tested in both longitudinal and transverse directions. The fiber-matrix interaction was investigated using scanning electron microscopy. The results showed that the fabrics prepared from Agave vera-cruz fibers as reinforcement in polyester gave better results in a less expensive material with superior quality and thermal resistance. For example, polyester composites reinforced with Agave vera-cruz fiber rope (vertical fabric) on the vertical direction had higher tensile strength (54.7 MPa), flexural strength (316.6 MPa), impact strength (109.6 kJ/m2), and barcol hardness (40) than the other three forms of the fibers (fiber random, fiber rope random, and horizontal direction fabric). In addition, Agave vera-cruz fiber rope vertical fabric had the lowest thermal conductivity (0.138 Wm−1 K−1) and the highest heat deflection temperature (77 °C) compared to the other three forms of the polyester composite. Prototypes of table tennis rackets and bicycle seats were successfully manufactured using polyester composites reinforced with woven Agave vera-cruz fiber fabric.